Personalized nutrition : - Kok, Frans. (CRC Press/Taylor & Francis, 2008)
Personalized nutrition is an emerging field that merges nutrition science with other disciplines, including molecular biology, biochemistry, and bioinformatics, to develop individual diets. Kok (nutrition and health, Wageningen University, The Netherlands) combines biomedical and social science perspectives to explore the molecular, physiological, epidemiological, and public health aspects of personalized nutrition, and gives examples from major diseases. The first section of the book, on scientific principles, discusses nutrigenomics technologies, such as transcriptomics, proteomics, and metabolomics, and their use in understanding the molecular mechanisms involved in major diet-related chronic disorders. The second section, on the consumer and society in personalized nutrition, compares five interest groups (scientists, food companies, consumers, competitive athletes, and healthcare providers) regarding their practices and opinions of personalized nutrition. A final section on examines humanitarian issues related to developing countries, and looks at personalized nutrition in the context of ongoing innovations in food technology, nutrigenomics, and food delivery systems